Heat transfer analysis in multi-configuration microchannel heat sink - Ghani, Ihsan Ali (2017)
In recent years, the use of passive techniques to enhance heat transfer in microchannel heat sink (MCHS) has received increasing attention due to escalating demand for improved thermal management in modern electronic designs. However, most studies concentrated on the use of one type of passive techniques that focuses only on one aspect of its performance which is either to acquire high rate of heat transfer with higher pressure drop, or gain low pressure drop at low rate of heat transfer. For further enhancement of hydrothermal performance in MCHS, this research combined two techniques to exploit features of high heat transfer in lower pressure drop. Three new configurations developed were numerically investigated, and experimentally validated. To assess the effects of various geometrical parameters, an optimization technique was used to calculate the most efficient geometry of the proposed designs. The first configuration is a combination between wavy channel and secondary channels (WMSC) etched on the channels walls. The attributes of this configuration are manifested in enhancing the flow mixing within main channels by Dean vortices and among adjacent channels through secondary channels. The results showed that the new design of WMSC has enhanced the overall thermal performance by 140% as compared with the straight MCHS. The second configuration is a combination between a sinusoidal grooves and rectangular ribs installed in the central portion of the channel (MC-SCRR). The flow area enlargement provided by the cavities has significantly reduced the pressure drop caused by the ribs. Besides, this configuration contributes to increase the heat transfer by inducing flow jet impingement and vortices as well as increasing the contact surface area. This design has achieved an enhancement of 85% more than the straight MCHS. The final configuration uses a combination of secondary oblique channels in alternating direction and rectangular ribs (MC-SOCRR). The new design has exploited a larger flow area which is provided by the secondary channels to reduce pressure drop caused by ribs, and increased the flow mixing between the main channels. These features have contributed to enhance the performance of MC-SOCRR by 98% more than the straight MCHS.